Role of fibrinogen in the attenuation of ischemia reperfusion and remote ischemic preconditioning - Mohamed S. A. Mohamed (Revista Colombiana de Cardiología, 2022)
Background: Ischemic reperfusion injury (IRI) is a common hazard involved in many human diseases, such as cerebral stroke, myocardial infarction, solid organ transplant dysfunction or failure, and vascular diseases. Understanding the molecular bases of this injury is essential for the prevention and control of these life-threatening conditions. Ischemic and remote ischemic preconditioning techniques (IPC and RIPC, respectively) have gained increasing importance in the clinical practice to protect against the IRI; however, the exact mechanisms of these techniques are not fully understood, which renders their clinical application query. Possible effectors: Nitric oxide (NO) has been reported by multiple studies to be an important mediator of the protective effects of those techniques. While the physiological concentrations of NO and fibrinogen (FB) are known to antagonize each other, the circulating levels of both effectors increase in response to RIPC. Hypothesis: While NO has potential anti-inflammatory effects, non-soluble fibrinogen (sFB) shows pro- inflammatory effects. However, the sFB may have the potential to act synergistically rather than antagonistically with NO toward the attenuation of the IRI. Conclusion: While increased FB is considered a risk factor for cardiovascular and inflammatory conditions that is also able to decrease the efflux of NO, and increase the NO oxidative metabolits and S- nitroglutathione, the increased sFB during the acute phase reaction might have other protective aspects that should be carefully investigated.